2012
DOI: 10.1007/s00345-012-0867-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the RENAL nephrometry score with warm ischemia time after robotic partial nephrectomy

Abstract: The A and L subcategories of the RNS have no significant impact on the WIT of patients undergoing RPN. WIT is significantly dependent upon the other subcategories, as well as the overall RNS. These findings can be used to preoperatively predict which tumor characteristics will likely affect WIT and may be useful in preoperative counseling as well as planning of approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 17 publications
4
22
0
2
Order By: Relevance
“…17 In their RPN series, Png and colleagues showed that complex tumours with a higher nephrometry scores had significantly high ischemic times compared with non-complex tumours. 11 In their minimally invasive PN case series, Liu and colleagues 18 and Altunrende and colleagues 9 found that nephrometry score was predictive of warm ischemic time, and mean warm ischemic time increased significantly by tumour complexity. Some data from OPN series also showed positive correlation of nephrometry score with warm ischemic time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In their RPN series, Png and colleagues showed that complex tumours with a higher nephrometry scores had significantly high ischemic times compared with non-complex tumours. 11 In their minimally invasive PN case series, Liu and colleagues 18 and Altunrende and colleagues 9 found that nephrometry score was predictive of warm ischemic time, and mean warm ischemic time increased significantly by tumour complexity. Some data from OPN series also showed positive correlation of nephrometry score with warm ischemic time.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, there is some debate on whether it can predict renal functional outcomes and surgery-related outcomes. 6,[9][10][11] Moreover, these studies mostly applied to the patients who underwent robotic partial nephrectomy (RPN) or laparoscopic partial nephrectomy (LPN), minimally invasive surgeries that used warm ischemia methods. In this study, we applied the nephrometry score to patients who underwent open partial nephrectomy (OPN) with cold ischemia and we confirm the usefulness of the nephrometry score to confirm postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…scores as well as the C-index [30] . As it has been shown that complex tumors often lead to increased ischemia time, especially in minimally invasive surgery procedures [31] , we since of late use them to intend surgical strategy preoperatively at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Long et al [5] conducted a retrospective review of data from 177 patients receiving PN and showed that an increased risk of conversion to radical nephrectomy and prolonged warm ischemia time (WIT) could be predicted by the RNS. However, there are limited data on the significance of the RNS in patients undergoing RAPN, and the outcomes are not consistent [12][13][14].…”
Section: Introductionmentioning
confidence: 97%